Design thinking approach to powerful material development in educational contexts: From theory to practice - Novawan, Adriadi; Ismailia, Titik; Zuhro, Cholimatus; Utami, Lely Dian; Pratama, Mudafiq Riyan; Karimah, Karimah; Haq, Rayya Nurrisqinia (International Journal of Studies in Social Sciences and Humanities (IJOSSH), 2024)
Design Thinking (DT), originating in industrial design, has evolved into a transformative framework for addressing global educational challenges, particularly in the development of teaching materials. By emphasizing empathy, ideation, and iterative prototyping, DT fosters creativity, collaboration, and adaptability, supporting active, interdisciplinary learning. However, challenges persist in integrating DT into curriculum design, pedagogy, and teaching materials, as well as evaluating its impact on student outcomes. This systematic literature review analyses the worldwide studies from 2010 to 2024 using a semi-systematic approach. Peer-reviewed literature from Scopus, Web of Science, and Google Scholar was examined through thematic analysis to identify DT’s principles, educational impacts, and implementation barriers. The findings demonstrate DT’s ability to enhance critical thinking, problem-solving, and engagement while aligning with technological and sustainability goals. Despite these benefits, institutional and cultural barriers, inadequate teacher training, and resource constraints limit its effectiveness. The review highlights the need for localized frameworks, integration of emerging technologies, and robust empirical research. Addressing these gaps can help educators create inclusive, innovative, and student-centred learning environments, equipping students with skills for an increasingly complex and globalized world.